Age-related vaginal microecology and infection epidemiology among premenopausal and postmenopausal gynecologic outpatients: a cross-sectional study - Wenyu Lin; Wenyu Lin; Wenyu Lin; Liying Wang; Liying Wang; Liying Wang; Binhua Dong; Binhua Dong; Binhua Dong; Yuhang Zhang; Yan Zhang; Liang Wang; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundPostmenopausal estrogen deficiency disrupts vaginal microecological balance. This cross-sectional study investigates the epidemiology of vaginal infections and alterations in microbiota composition, enzymes, and metabolites among premenopausal and postmenopausal gynecologic outpatients.MethodsThe study analyzed the vaginal microecology data from 27,346 women who underwent examinations at Fujian Maternity and Child Health Hospital between 2018 and 2023. Parameters including vaginal cleanliness, bacterial density, and diversity were systematically evaluated. Additionally, a total of 20 participants (10 premenopausal and 10 postmenopausal women) were enrolled for nontargeted LC-MS metabolomic analysis through stratified random sampling.ResultsThe population comprised 22,525 (82.4%) premenopausal women (18–44 years), 3,456 (12.6%) transitioning women (45–55 years), and 1,365 (5.0%) postmenopausal women (>55 years). In mixed infections, BV + VVC co-infections predominated (1264/2766, 45.7%). Postmenopausal women showed significantly higher BV prevalence (22.8% vs. 17.9%, P < 0.001) and AV (24.8% vs. 4.6%, P < 0.001), but lower rates of VVC (1.2% vs. 8.2%, P < 0.001). In postmenopausal women, BV-associated biomarkers (including clue cells and sialidase activity) and inflammatory markers (such as pus cells and leukocyte esterase activity) were concurrently elevated. Metabolomic analysis identified elevated chenodeoxycholic acid glycine conjugate levels alongside reduced O-phosphothreonine, morpholine, and diethanolamine.ConclusionAge significantly influences vaginal microecology, altering infection epidemiology, microbiota, enzymes, and metabolites. Accounting for these age-related estrogen changes in clinical interventions is critical for effective management.